Desentralisasi dan Komitmen Organisasi sebagai Pemoderasi Hubungan antara Partisipasi Penyusunan Anggaran dan Kinerja Manajerial pada Perguruan Tinggi Swasta di Indonesia - Coryanata, Isma (Journal of Accounting and Investment, 2006)
The result of previous studies on the relationship between budget  participation and managerial performance has been inconclusive and often contradictory. To resolve these differences, Govindrajan (1986a) states that it needs contingency approach. This approach systematically evaluated various conditions or factors that attain effect relation between budget  participation and managerial performance. This study empirically examined effect relation between budget  participation and managerial performance using two variables of contingency, namely decentralization and organizational commitment. Mailed questionnaires were distributed to 1000 managers from private universities in Indonesia by stratified sampling. The responses from 89 managers (8,9%) were analyzed by using regression analysis. The result indicated that the interaction between decentralization, organizational commitment,  and budget participation affected managerial performance on private universities.